Virtues Suffice for Argument Evaluation - Aberdein, Andrew (Informal Logic)

(untitled) (Informal Logic, 2023)
The virtues and vices of argument are now an established part of argumentation theory. They have helped direct attention to hitherto neglected aspects of how we argue. However, it remains controversial whether a virtue theory can contribute to some of the central questions of argumentation theory. Notably, Harvey Siegel disputes whether what he calls ‘arguments in the abstract propositional sense’ can be evaluated meaningfully within a virtue theory. This paper explores the prospects for grounding an account of argument evaluation in arguers’ virtues and vices by examination of a corresponding debate in virtue ethics: Can an ethics of virtue guide our actions? It is thereby argued that an affirmative answer is possible: virtues suffice for argument evaluation.